2018
DOI: 10.1007/s10120-018-0902-2
|View full text |Cite
|
Sign up to set email alerts
|

Number of retrieved lymph nodes is an independent prognostic factor after total gastrectomy for patients with stage III gastric cancer: propensity score matching analysis of a multi-institution dataset

Abstract: Background The prognostic significance of the number of retrieved lymph nodes (RLNs) in gastric cancer remains controversial. Therefore, we designed a multicenter collaborative database to investigate the correlation between the number of RLNs and prognosis of patients with advanced gastric cancer after curative resection. Methods We retrospectively analyzed 1103 patients who underwent gastrectomy for stage II/III gastric cancer between 2010 and 2014. Lymph nodes, which were retrieved by surgeons from surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…Many studies have suggested that overall survival (OS) is associated with the number of retrieved lymph nodes (RLNs) (1)(2)(3). The results based on data from the Surveillance, Epidemiology, and End Results (SEER) database showed that OS was dependent on the number of RLNs (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have suggested that overall survival (OS) is associated with the number of retrieved lymph nodes (RLNs) (1)(2)(3). The results based on data from the Surveillance, Epidemiology, and End Results (SEER) database showed that OS was dependent on the number of RLNs (1).…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of RLNs cannot separate the impact of stage migration versus improved regional disease control to favor survival. Recently, Hayashi et al showed that the number of RLNs < 40 could be attributed to an inferior survival for stage III gastric cancer (GC) patients who underwent total gastrectomy (2). Consistently, another large international dataset analysis, including the SEER database (n = 13,932) and the Yonsei University Gastric Cancer database (n = 11,358), also proposed that a greater number of RLNs (a minimum of 29) improves staging and OS in GC patients undergoing radical resection (3).…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al suggested that the ELN number should be greater than 25 for patients with advanced gastric cancer 22 . Hayashi et al assessed gastric cancer patients who underwent total gastrectomy at stage III, and the results showed that an ELN number > 40 was associated with the patients' prolonged OS and RFS 23 . Although the above studies identified ELN number as an independent risk factor for patients with gastric cancer, there were discrepancies among the included populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the optimal number of retrieved LNs remains controversial. For example, Hayashi et al [13] recommended retrieval of > 40 LNs after total gastrectomy for stage III patients, whereas Lu et al [12] suggested that harvesting 21 LNs might represent a superior cut-off point for radical total gastrectomy to better determine the prognosis of the patients. Although a greater number of retrieved LNs has been associated with longer survival of patients with node-metastatic cancer, the optimal number of LNs to be examined at different stages remains unclear.…”
Section: Discussionmentioning
confidence: 99%